SOCIO-CUL TURAL DYNAMICS OF MURIDIZM MOVEMENT IN CAUCASIA - Demirpolat, Anzavur (Fırat University, 2007)
Although much has been written on Sufısm, . there are only some sources or writings evaluating the dynarnics of Muridizm mavement in Circassia in relation with Naqshbandi Sufism. Therefore, the aim of this study is to compensate such a shortage through analyzing the dynamics of Muridizm movement. Such an aim requires elucidating, on the one hand, the geopolitical, socio-cultural structure of Circassia, on the other hand, the religious and more particularly, the Sufi grounds of Muridizm movement. Although the acceptance of Islam by all the Circassian tribes was very Iate, all native tribes except Georgians and Armenians had become Muslim during the eighteenth century. From the early leader of the movement, namely Imam Mansur, to Sheik Shamil, Naqshbandism was very successful and effective in that region in terms of organizing as well as uniting all Circassian tribes under the banner of Islam and Muridizın against the Russian troops and their invasions. In this study, my principal thesis is as follows: there were at least two main factors behind the success of the Muridizm movement; they were Naqshbandi Sufism and tribal "asabiyya". Both amalgamated and brought unity for all Circassian tribes to struggie against Russian Empire. Consequently, this study aims to evaluate these two dimensions in co Ilaboration with each oth-er.

Although much has been written on Sufısm, . there are only some sources or writings evaluating the dynarnics of Muridizm mavement in Circassia in relation with Naqshbandi Sufism. Therefore, the aim of this study is to compensate such a shortage through analyzing the dynamics of Muridizm movement. Such an aim requires elucidating, on the one hand, the geopolitical, socio-cultural structure of Circassia, on the other hand, the religious and more particularly, the Sufi grounds of Muridizm movement. Although the acceptance of Islam by all the Circassian tribes was very Iate, all native tribes except Georgians and Armenians had become Muslim during the eighteenth century. From the early leader of the movement, namely Imam Mansur, to Sheik Shamil, Naqshbandism was very successful and effective in that region in terms of organizing as well as uniting all Circassian tribes under the banner of Islam and Muridizın against the Russian troops and their invasions. In this study, my principal thesis is as follows: there were at least two main factors behind the success of the Muridizm movement; they were Naqshbandi Sufism and tribal "asabiyya". Both amalgamated and brought unity for all Circassian tribes to struggie against Russian Empire. Consequently, this study
SOCIO-CUL TURAL DYNAMICS OF MURIDIZM MOVEMENT IN CAUCASIA
Keywords: Religious Studies; Din Araştırmaları